STUDI KESEIMBANGAN ADSORPSI MERKURI(II) PADA BIOMASSA DAUN ENCENG GONDOK (Eichhornia crassipes) - Al-ayubi, Muhammad Chalid; Barroroh, Himmatul; Dewi, Diana Candra (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2010)
Metal ion adsorption research with utilizing Eichhornia crassipes leaf biomass has been done. Metal ions which are ever researched are Cr, Cd, Pb and Ni, but research with utilizing Hg metal ion is never done, so need to be implemented a mercury adsorption research to eichhornia crassipes leaf biomass. Because pH solution is very influential to metal ion adsorption by biomass, so in this research is inspected determining of optimum pH to mercury adsorption. This research is experimental research which is started with determining of optimum pH, this determining of optimum pH is implemented with way of interacting 60 mmg/L mercury metal ion with 0,1 gr eichhornia crassipes leaf biomass for 60 minutes at range of pH 2, 3, 4, 5, 6, 6, 4, 6, 7, 7 and 8, then continued with control solution production to know the solubility of mercury in every pH. The determination of adsorption capacity, adsorption constanta and adsorption energy are implemented with way of interacting eichhornia crassipes leaf biomass with mercury metal ion by 20, 30, 40, 50, 60, 70, 80, 90, 100 and 150 mmg/L variation of concentration for 60 minutes in pH optimum. Data the result of experiment then processed using the similarity of Langmuir isotherm and Freunlich.. The result of the research indicates that pH 6 is mercury adsorption optimum pH in eichhornia crassipes leaf biomass. The mercury isotherm adsorption in eichhornia crassipes leaf biomass takes a part of the similarity of langmuir isotherm with point R2 = 0,982, from the similarity of langmuir isotherm gotten adsorption capacity (Xm) in the mount of 4, 806 x 10-5 mol/gr with adsorption constanta (K) 27130,85 mol/L and adsorption energy (E) in the mount of 25,46079 kJ/mol.